Transplantation of tissue engineering neural network and formation of neuronal relay into the transected rat spinal cord. (December 2016) - Lai, Bi-Qin; Che, Ming-Tian; Du, Bao-Ling; Zeng, Xiang; Ma, Yuan-Huan; Feng, Bo; Qiu, Xue-Chen; Zhang, Ke; Liu, Shu; Shen, Hui-Yong; Wu, Jin-Lang; Ling, Eng-Ang; et al.
Abstract: Severe spinal cord injury (SCI) causes loss of neural connectivity and permanent functional deficits. Re-establishment of new neuronal relay circuits after SCI is therefore of paramount importance. The present study tested our hypothesis if co-culture of neurotrophin-3 (NT-3) gene-modified Schwann cells (SCs, NT-3-SCs) and TrkC (NT-3 receptor) gene-modified neural stem cells (NSCs, TrkC-NSCs) in a gelatin sponge scaffold could construct a tissue engineering neural network for re-establishing an anatomical neuronal relay after rat spinal cord transection. Eight weeks after transplantation, the neural network created a favorable microenvironment for axonal regeneration and for survival and synaptogenesis of NSC-derived neurons. Biotin conjugates of cholera toxin B subunit (b-CTB, a transneuronal tracer) was injected into the crushed sciatic nerve to label spinal cord neurons. Remarkably, not only ascending and descending nerve fibers, but also propriospinal neurons, made contacts with b-CTB positive NSC-derived neurons. Moreover, b-CTB positive NSC-derived neurons extended their axons making contacts with the motor neurons located in areas caudal to the injury/graft site of spinal cord. Further study showed that NT-3/TrkC interactions activated the PI3K/AKT/mTOR pathway and PI3K/AKT/CREB pathway affecting synaptogenesis of NSC-derived neurons. Together, our findings suggest that NT-3-mediated TrkC signaling plays an essential role in constructing a tissue engineering neural network thus representing a promising avenue for effective exogenous neuronal relay-based treatment for SCI.